2000
DOI: 10.1097/00005792-200009000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Visual Manifestations of Giant Cell Arteritis: Trends and Clinical Spectrum in 161 Patients

Abstract: Giant cell (temporal) arteritis (GCA) is the most common systemic vasculitis in Western countries. It involves large and medium-sized vessels with predisposition to the cranial arteries in the elderly. Cranial ischemic complications, in particular permanent visual loss, constitute the most feared aspects of this vasculitis. Although the use of corticosteroids and a higher physician awareness may have contributed to a decrease in the frequency of severe ischemic complications, permanent visual loss is still pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
195
7
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 355 publications
(224 citation statements)
references
References 33 publications
16
195
7
6
Order By: Relevance
“…In our series, the proportion of patients who developed permanent visual loss (19.1%) was similar to that reported by Gonzalez-Gay et al (2,12) and by Cid et al (9) (2,3,9,11). Although geographic and ethnic factors may be implicated in the differences in the incidence of GCA at different latitudes, they do not seem to influence the expression of visual manifestations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our series, the proportion of patients who developed permanent visual loss (19.1%) was similar to that reported by Gonzalez-Gay et al (2,12) and by Cid et al (9) (2,3,9,11). Although geographic and ethnic factors may be implicated in the differences in the incidence of GCA at different latitudes, they do not seem to influence the expression of visual manifestations.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, similarly to our study, an increased risk of developing visual loss was observed in patients with thrombocytosis at diagnosis. Gonzàlez-Gay et al demonstrated an association between the absence of fever and weight loss, on the one hand, and permanent visual loss, on the other; however, acute-phase reactants did not differ significantly between those with visual loss and those without (2,12). These authors also observed a negative association between anemia (Hgb Ͻ12 gm/dl) and the development of severe ischemic manifestations (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vasculitic involvement of these arteries leads to the typical symptoms and classic clinical features of GCA such as bitemporal headache, jaw claudication, scalp tenderness, or abnormal temporal arteries (tender, nodular, swollen, and thickened arteries with decreased pulses) on physical examination (3). However, ocular ischemic complications, the most feared complications of this vasculitis, are generally early manifestations due to the vasculitic involvement of ocular vessels deriving from the internal carotid artery (4). In unselected patients with biopsy-proven GCA, visual ischemic complications occur in 25% and irreversible visual loss occurs in 10 -15% of the patients (4).…”
Section: Epidemiology Of Gca and Pmrmentioning
confidence: 99%
“…However, ocular ischemic complications, the most feared complications of this vasculitis, are generally early manifestations due to the vasculitic involvement of ocular vessels deriving from the internal carotid artery (4). In unselected patients with biopsy-proven GCA, visual ischemic complications occur in 25% and irreversible visual loss occurs in 10 -15% of the patients (4). They are generally due to anterior ischemic optic neuropathy that is caused by interruption of blood flow in the posterior ciliary arteries to the optic nerve head.…”
Section: Epidemiology Of Gca and Pmrmentioning
confidence: 99%